FORMATION OF INFORMATION AND COMMUNICATION COMPETENCE OF THE TEACHER AS AN ONE OF THE MAIN TASKS OF MODERN EDUCATION (Academia Science Repository, 2023)
Currently, information technology is a necessary addition to the traditional educational process in general education schools. In the educational process of the school, electronic textbooks, notebooks, textbooks, didactic materials, simulators, testing systems, electronic libraries, catalogs, information resources of the Internet, etc. are often used. The formation of a teacher's information competence is a guarantee of professional development. competence as a factor in improving the quality of education. The article examines the formation of professional competence of teachers in the context of informatization of society. The article examines the formation of professional competence of teachers in the context of informatization of society. At the same time, the concepts of information competence are analyzed and the stages of the formation of professional information competence of teachers are given.